1986
DOI: 10.1515/cclm.1986.24.6.361
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effects of Betamethasone, L-Carnitine, and Betamethasone-L-Carnitine Combinations on the Dipalmitoyl Phosphatidylcholine Content and Phosphatidylcholine Species Composition in Foetal Rat Lungs

Abstract: Summary: Administration of L-caniitine or betamethasone to pregnant rats failed to increase either the total phospholipid or dipalmitoylphosphatidylcholine (DPPC) contents in foetal rat lungs on the 20th day of j gestation, eompared to cpntrols. The combined administration of betamethasone (0.3 mg/kg) and L-carnitine ; (80 mg/kg) resulted in a pronounced increase of dipalmitoylphosphatidylcholine (7.8 ±2.5 mg/g dry weight) j coinpared with the control group (5.4 ± 1.8 mg/g dry weight), and compared with the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Obviously there are specific effects of a carnitine-thyroxine combination compared with the effects of carnitine or thyroxine treatment. In a former study we showed that carnitine potentiated the effects of betamethasone on DPPC content of fetal rat lungs (7). Therefore, treatment with a carnitine combination may be of more benefit decreasing the incidence of respiratory distress syndrome than the administration of thyroxine (or betamethasone) alone.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Obviously there are specific effects of a carnitine-thyroxine combination compared with the effects of carnitine or thyroxine treatment. In a former study we showed that carnitine potentiated the effects of betamethasone on DPPC content of fetal rat lungs (7). Therefore, treatment with a carnitine combination may be of more benefit decreasing the incidence of respiratory distress syndrome than the administration of thyroxine (or betamethasone) alone.…”
Section: Resultsmentioning
confidence: 95%
“…P C 32 monoenic species. The PC 32 monoenic species can be characterized as palmitoyl-palmitoley1 PC ( 16:0/ 16: 1 PC) and palmitoleyl-palmitoy1 PC (16: 1/16:0 PC) (6). The portion of palmitoyl-palmitoleyl PC in total PC decreased significantly (p < 0.01) after the combined administration of thyroxine and carnitine in comparison with the control value.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…phospholipids and also the formation of lecithin via methylation could be stimulated by carnitine. In animal experiments, LOHNIN-GER and coworkers were able to show that the combination of carnitine and betamethasone due to their different mechanisms, leads to a larger increase of phosphatidylcholin in the lung of the fetal rat than single dosages of the two substances [8]. Comparable results were found in the carnitine/thyroxin group.…”
Section: Ambroxolmentioning
confidence: 97%